2016
DOI: 10.1016/j.biomaterials.2015.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of lung cancer recurrence using cisplatin-loaded superhydrophobic nanofiber meshes

Abstract: For early stage lung cancer patients, local cancer recurrence after surgical resection is a significant concern and stems from microscopic disease left behind after surgery. Here we apply a local drug delivery strategy to combat local lung cancer recurrence after resection using non-woven, biodegradable nanofiber meshes loaded with cisplatin. The meshes are fabricated using a scalable electrospinning process from two biocompatible polymers—polycaprolactone and poly(glycerol monostearate-co-caprolactone)—to aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(87 citation statements)
references
References 50 publications
0
87
0
Order By: Relevance
“…Recently, the therapeutic treatments have made great progress; however, the prognosis for patients with NSCLC remains poor and the five-year overall survival rate is only 15% (6). An increasing number of evidences indicated that tumor metastasis and recurrence are frequent, and huge challenges in the therapy of NSCLC, and mostly responsible for the low five-year survival rate (7)(8)(9)(10). Cumulatively, this highlights the urgent need to fully understand the mechanism on NSCLC formation and progression and identify novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the therapeutic treatments have made great progress; however, the prognosis for patients with NSCLC remains poor and the five-year overall survival rate is only 15% (6). An increasing number of evidences indicated that tumor metastasis and recurrence are frequent, and huge challenges in the therapy of NSCLC, and mostly responsible for the low five-year survival rate (7)(8)(9)(10). Cumulatively, this highlights the urgent need to fully understand the mechanism on NSCLC formation and progression and identify novel therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…in the Grinstaff laboratory [221] investigated the release of cisplatin from electrospun superhydrophobic meshes, again using PCL and PGC-C18 polymer blends. Drug release and extended cytotoxicity against Lewis Lung Carcinoma (LLC) cells is observed over 90 days, which corresponded to the infiltration time for a solution of 10% fetal bovine serum (FBS), as imaged by CT. To our knowledge, this is the longest reported underwater layer maintenance in the presence of significant protein.…”
Section: Drug Deliverymentioning
confidence: 99%
“…24,27,28 While an earlier study 29 partly demonstrated the effect of drug-polymer-solvent compatibility on drug release proles, further analytical work is necessary to explain the phenomena. Of major interest of this study is to: (1) investigate the inuence of drug-polymer miscibility on the drug release proles from hydrophobic ber mats; (2) analyze the drug localization in the polymeric matrix; and (3) examine the effectiveness of drug delivery by in vitro cytotoxicity assay. Drug-loaded ber mats were prepared by electrospinning of solution precursors containing poly(lactic acid) (PLA) and either hydrophilic Dox (DoxHCl) or hydrophobic Dox (Dox-base).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] Of the ber-forming processes, electrospinning has been widely adopted as a versatile method to produce brous vehicles with ne-tuned morphology for effective delivery of therapeutic agents. [1][2][3]5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] For example, multi-axial electrospinning has been utilized to produce multi-compartmental bers that allow multiple release stages or multi-drug delivery. 5,10,18 This conguration has a potential application of treating patients who have developed resistance to specic drugs.…”
Section: Introductionmentioning
confidence: 99%